The Impact of Adopting Internal Marketing Concept and Procedures in Higher Education Institutions on the Performance of University Professor - From the Point of View of a Sample of Professors University - - براهيمي سمير (Finance and Business Economies Review, 2021)
This study aimed to highlight the impact of adopting the concept and procedures of internal marketing on the performance of the university professor, and in order to achieve this goal the researcher prepared an electronic questionnaire and sent it to a sample of 385 university professor distributed inside seven colleges of economic, commercial and management sciences in universities: Chlef, El Ouedi, Khenchela, Skikda, Bordj Bou Arreridj, Djelfa, Oum El Bouaghi. The study found: The existence of a statistically significant correlation between internal marketing and the performance of the university professor amounted to 0,368. The presence of a statistically significant effect of internal marketing on the performance of the university professor from the university professors’ point of view.